2010
DOI: 10.1002/ceat.200900453
|View full text |Cite
|
Sign up to set email alerts
|

Model for Calculation of Agglomerate Sizes of Nanoparticles in a Vibro‐fluidized Bed

Abstract: The behavior of SiO 2 nanoparticles and the effects of operating conditions on nanoparticle agglomerate sizes have been investigated under conditions created in a vibro-fluidized bed (VFB). The experimental results reveal that the vibrations imposed in the bed can suppress slugging and/or channeling, in contrast to conventional fluidization with upflow only. The vibrations imposed in the particle bed affect both the minimum fluidization velocity and the agglomerate size, both of which decrease with increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Nam et al [5] developed a fractal analysis combined with a modified RichardsonZaki for prediction of agglomerate size of nanoparticle agglomerates. Wang et al [6] estimated agglomerate sizes of SiO 2 nanoparticles according to the Richardson-Zaki scaling law combined with Stokes law permits, and the average agglomerate sizes calculated were in agreement with those determined experimentally. Kaliyaperumal et al [2] determine the apparent minimum fluidization velocity from pressure drop signals by employing a novel technique, at the same time, using Richardson-Zaki equation to show agglomerate fluidization behavior.…”
Section: Introductionsupporting
confidence: 67%
“…Nam et al [5] developed a fractal analysis combined with a modified RichardsonZaki for prediction of agglomerate size of nanoparticle agglomerates. Wang et al [6] estimated agglomerate sizes of SiO 2 nanoparticles according to the Richardson-Zaki scaling law combined with Stokes law permits, and the average agglomerate sizes calculated were in agreement with those determined experimentally. Kaliyaperumal et al [2] determine the apparent minimum fluidization velocity from pressure drop signals by employing a novel technique, at the same time, using Richardson-Zaki equation to show agglomerate fluidization behavior.…”
Section: Introductionsupporting
confidence: 67%
“…It was found that agglomerate structure properties are insensitive to the R-Z exponent, whereas the minimum fluidization velocity is sensitive to this parameter. [7] Present work Nam et al [14] Zhu et al [7] Wang et al [36] R974 …”
Section: Discussionmentioning
confidence: 96%
“…Many methods were developed to improve the fluidization behavior of nanoparticles, for example, adding coarse particles to the bed [9][10][11] and introducing a magnetic field [12][13][14], acoustic field [15,16], or vibrating field [17][18][19]. Contrasted with other methods, the advantage of adding coarse particles is that it is unnecessary to get additional equipment or devices.…”
Section: Introductionmentioning
confidence: 99%